Routine urinary detection of antihypertensive drugs for systematic evaluation of adherence to treatment in hypertensive patients - Hamdidouche, Idir; Jullien, Vincent; Boutouyrie, Pierre; Billaud, Eliane; Azizi, Michel; Laurent, Stéphane (Journal of hypertension, 2017)
Nonadherence to antihypertensive therapy is an important cause of poor blood pressure control. However, to date, few effective and accurate tools exist to routinely evaluate drug nonadherence. In this observational study, performed under conditions of routine clinical practice, we included 174 patients (aged 67 ± 11 years) with treated essential hypertension who attended the outpatient hypertension clinic of a university hospital. Adherence to antihypertensive treatment was measured by using ultraperformance liquid chromatography-tandem mass spectrometry in spot urine at the time of clinical appointment and blood pressure measurement. Patients were also asked to report their adherence using a validated questionnaire (four-item Morisky Medication Adherence Scale). The prevalence of directly measured nonadherence by urine drug detection was approximately 10%. Compared with adherent patients, those who did not adhere to their treatment (n = 15) had a higher number of antihypertensive pills and drugs (P = 0.02), cotreatment with cardiovascular drugs (P < 0.05), and total concurrent medications and pills (P < 0.01). After adjustment for age, SBP and DBP were higher in nonadherent than adherent group (SBP: 146 ± 18 vs. 131 ± 14, respectively, P < 0.01; and DBP: 77 ± 15 vs. 73 ± 9, respectively, P < 0.01). There was no significant association between four-item Morisky Medication Adherence Scale score and directly measured nonadherence. A longitudinal analysis, performed in a subpopulation of 105 patients after a median follow-up of 11 months, showed that the adherence status remained unchanged in 88% of patients. These results indicate a good adherence to antihypertensive drugs in patients attending the outpatient clinics of a university hospital. They suggest that urine detection of antihypertensive drugs by ultraperformance liquid chromatography-tandem mass spectrometry is an accurate and practical tool for directly monitoring adherence. This direct information is not overlapping with self-report questionnaire.